2022
DOI: 10.3389/fcell.2022.918760
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Lamin A/C in the Regulation of Nav1.5 Channel and Microtubules: Lesson From the Pathogenic Lamin A/C Variant Q517X

Abstract: In this work, we studied an lmna nonsense mutation encoding for the C-terminally truncated Lamin A/C (LMNA) variant Q517X, which was described in patients affected by a severe arrhythmogenic cardiomyopathy with history of sudden death. We found that LMNA Q517X stably expressed in HL-1 cardiomyocytes abnormally aggregates at the nuclear envelope and within the nucleoplasm. Whole-cell patch clamp experiments showed that LMNA Q517X-expressing cardiomyocytes generated action potentials with reduced amplitude, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We also found that the severity of the clinical manifestations in cardiac laminopathy patients harboring different pathogenic Lmna variants, correlates with the degree of inflammation in terms of numbers of pro-inflammatory cytokines upregulated, thus suggesting an immediate therapeutic approaches for each subset of patients (12). Moreover, we recently showed that a well-known FDA-approved alkaloid, colchicine, recovered the altered tubulin polymerization state as well as the dysfunctional electrical properties in cardiomyocytes expressing a pathogenic LMNA variant (13).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We also found that the severity of the clinical manifestations in cardiac laminopathy patients harboring different pathogenic Lmna variants, correlates with the degree of inflammation in terms of numbers of pro-inflammatory cytokines upregulated, thus suggesting an immediate therapeutic approaches for each subset of patients (12). Moreover, we recently showed that a well-known FDA-approved alkaloid, colchicine, recovered the altered tubulin polymerization state as well as the dysfunctional electrical properties in cardiomyocytes expressing a pathogenic LMNA variant (13).…”
Section: Introductionmentioning
confidence: 80%
“…This finding suggests that the pathogenetic mechanism of the cardiomyopathy in the nonsense mutation group might be related to either the dominant negative effect or cytotoxic effect of the resulting truncated LMNA protein rather than exclusively haploinsufficiency of LMNA wild type. Accordingly, we and others demonstrated that truncated pathogenic variants of LMNA were expressed into the heart of the carriers and may induce abnormal degradation of the WT LMNA (16) or interfere with cardiomyocytes homeostasis (17); (18); (13). Specifically, we previously characterized nonsense Lmna mutation that introduces a premature termination codon within the 6th of 12 Lmna exons corresponding to a truncated variant in the central a-helical coiled-coil rod domain (coil 2B) of the LMNA protein, R321X.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the deletion and truncation mutants of LMNA also form aggregates in the nucleoplasm. Aggregation of LMNA Q517X has been reported to correlate with hyperacetylation of tubulins, which tend to hyper‐polymerize in the form of microtubules, resulting in a reduced presence of the Nav1.5 channel at the cell surface in cardiomyopathic cells 174 . Loss of LMNA expression is also a common phenotype observed in probands with homozygous and heterozygous truncation mutations in LMNA .…”
Section: Mechanisms Of Proteostasis Failure and Proteotoxicity In Lam...mentioning
confidence: 99%
“…Aggregation of LMNA Q517X has been reported to correlate with hyperacetylation of tubulins, which tend to hyper-polymerize in the form of microtubules, resulting in a reduced presence of the Nav1.5 channel at the cell surface in cardiomyopathic cells. 174 Loss of LMNA expression is also a common phenotype observed in probands with homozygous and heterozygous truncation mutations in LMNA. For example, the Q6Ter [c.16C>T] mutation in LMNA showed very low expression of LMNA in myocardial tissue in several members of a related family with reports of cardiomyopathy and musculoskeletal defects.…”
Section: Proteostasis Failure and Proteotoxicity In Laminopathiesmentioning
confidence: 99%
“…Moreover, we recently showed that a well-known FDA-approved alkaloid, colchicine, recovered the altered tubulin polymerization state as well as the dysfunctional electrical properties in cardiomyocytes expressing a pathogenic LMNA variant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%